Human Development Transformation Towards Poverty Levels In Balocci District, Pangkajene And Islands Regency (Pangkep) - Iskandar, Muh Resky; Utami, Ayu Wandika Putri; Haerani, Andi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Balocci District in Pangkajene and the Islands Regency (Pangkep) boasts significant natural resource potential, yet still faces significant challenges in poverty alleviation. Despite efforts to improve welfare through infrastructure development and social programs, the quality of life of the Balocci community remains suboptimal. The Human Development Index (HDI), which measures health, education, and income, still needs improvement to reduce poverty. The urgency of this research is driven by the need for empirical data to support the formulation of poverty alleviation policies based on improving the quality of education, health, and income. This study aims to analyze the relationship between increasing the HDI and reducing the poverty rate in Balocci District. This research identifies factors influencing poverty and provides recommendations for strategic policies that can improve community welfare through human development. By understanding the mechanisms by which the HDI influences poverty, it is hoped that more targeted and effective intervention programs can be designed. The method used in this study is multiple linear regression to examine the effect of the HDI on poverty rates in Balocci District. Data processing techniques were performed using statistical software (e.g., SPSS or AMOS) to test the significance of variable relationships, identify classical assumptions such as normality, multicollinearity, and autocorrelation, and separate direct and indirect effects. Data were obtained from official publications of the Pangkep Regency Statistics Agency (BPS) and other official sources. Targeted outputs include policy recommendations for practitioners and local governments in poverty alleviation efforts by improving the quality of the HDI